THE INFLUENCE OF THE COMPETENCE OF THESIS SUPERVISOR OF COMMUNICATION SCIENCE UNJ ON STUDENTS' MOTIVATION IN COMPILING THESIS - Sianipar, Ladisa Naftania (Universitas Sang Bumi Ruwa Jurai, 2025)
Â This research aims to determine the influence of the competence of thesis supervisors on student motivation in writing theses at the Jakarta State University (UNJ) Communication Science Study Program. The method used in this research is a quantitative approach with survey techniques. Data was collected by distributing questionnaires to 100 students who were in the process of writing their thesis. Data analysis was carried out using simple linear regression to test the influence of supervisory lecturer competence on student motivation. The research results show that there is a significant positive influence between the competence of supervisors and student motivation. The higher the competence of the supervisor, the higher the students' motivation to complete their thesis. The average supervisory lecturer competency score is in the